Public engagement with science defining the project - Potochnik, Angela (Cambridge elements. Elements in public engagement with science, 2025)
'Public engagement with science' is gaining currency as the framing for outreach activities related to science. However, knowledge bearing on the topic is siloed in a variety of disciplines, and public engagement activities often are conducted without support from relevant theory or familiarity with related activities. This first Element in the Public Engagement with Science series sets the stage for the series by delineating the target of investigation, establishing the importance of cross-disciplinary collaboration and community partnerships for effective public engagement with science, examining the roles public engagement with science plays in academic institutions, and providing initial resources about the theory and practice of public engagement with science. Useful to academics who would like to conduct or study public engagement with science, but also to public engagement practitioners as a window into relevant academic knowledge and cultures. This title is also available as Open Access on Cambridge Core.